1998
DOI: 10.1111/j.1442-200x.1998.tb01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol or mist in acute bronchiolitis

Abstract: Background: The role of bronchodilators in the treatment of bronchiolitis remains controversial. M e t M : A double-blind, placebo controlled trial was performed to evaluate the clinical response to nebulized salbutamol. One hundred and fifty-six infants aged between 7 weeks and 24 months who had had an episode of wheezing and other signs and symptoms of bronchiolitis were randomized to three groups as follows: (i) nebulized salbutamol was administered to 52 patients in group I at a dose of 0.15 mgkg in 2 mL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 19 publications
0
37
1
Order By: Relevance
“…In three of these studies, some difference had been observed [3,11,12], yet it resulted in only a small transient improvement in the acute clinical score and had no effect on hospital admission rates or duration of stay in hospital. In one of these three studies [11], ex-premature infants who might have had some mild underlying chronic lung disease, which might have resulted in the response to bronchodilators, were not excluded.…”
Section: Salbutamol Albuterol and Ipratropium Bromidementioning
confidence: 99%
See 2 more Smart Citations
“…In three of these studies, some difference had been observed [3,11,12], yet it resulted in only a small transient improvement in the acute clinical score and had no effect on hospital admission rates or duration of stay in hospital. In one of these three studies [11], ex-premature infants who might have had some mild underlying chronic lung disease, which might have resulted in the response to bronchodilators, were not excluded.…”
Section: Salbutamol Albuterol and Ipratropium Bromidementioning
confidence: 99%
“…In one of these three studies [11], ex-premature infants who might have had some mild underlying chronic lung disease, which might have resulted in the response to bronchodilators, were not excluded. Several studies reported an increase in heart rate [12] or a decrease in oxygen saturation [3] after salbutamol or albuterol.…”
Section: Salbutamol Albuterol and Ipratropium Bromidementioning
confidence: 99%
See 1 more Smart Citation
“…Although commonly used, 5 its efficacy is not universally accepted. Small studies 6–9 and systematic reviews have shown small, short‐term improvement in clinical scores in outpatient use of albuterol 10 . There is, however, no convincing evidence that albuterol decreases the admission rate in outpatients 10 .…”
mentioning
confidence: 99%
“…Seventeen studies obtained chest x-ray films on all patients (Table 5), 7,12,19,20,28,[30][31][32][33][34][35][36][37][38][39][40][41] but many clinical trials do not report chest x-ray film results. Two studies examined the relationship between x-ray film abnormalities and disease severity.…”
Section: Utility Of Chest X-rays In Bronchiolitismentioning
confidence: 99%